2022
DOI: 10.30574/gscbps.2022.21.2.0427
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen therapies and the benefits for menopausal and perimenopausal women: An aphoristic review

Abstract: Women account for half of the global population, yet, when applying of the principles of legislation to women's health and gender-based research there is a void pertaining to women-specific healthcare as they age. Hydrogen therapies such as oxy-hydrogen (HHO, H2/O2) inhalation act as a novel, non-toxic, antioxidant and anti-inflammatory compounds, with clinical and empirical research confidently suggesting such therapies may be beneficial to human reproductive health. This aphoristic review highlights the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Another action mechanism reported that H 2 acts similarly to estrogen derivatives by upregulating the endogenous expression of antioxidant enzymes and peptides as an antioxidant [ 32 ]. During the late luteal phase of the menstrual cycle, estrogen hormone levels are low in preparation for menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Another action mechanism reported that H 2 acts similarly to estrogen derivatives by upregulating the endogenous expression of antioxidant enzymes and peptides as an antioxidant [ 32 ]. During the late luteal phase of the menstrual cycle, estrogen hormone levels are low in preparation for menstruation.…”
Section: Discussionmentioning
confidence: 99%